Eric Berne - Stewart, Ian, 1940- (London : Sage, 1992)
Part of the "Key Figures in Psychotherapy" series, this text chronicles the life, contributions and influence of Eric Berne, founder of Transactional Analysis counselling.
Bibliography: p150-155. - Includes index.
Keywords: Berne, Eric; Counseling -- History; Psychotherapy -- History